Study of Corrosion in Diesel Engine Piston by Soybean Biodiesel and its Mixtures - Fernanda Beatriz Aires de Freitas; Daniel Freitas Freire Martins; Antonio Alex de Lima Silva (Orbital: The Electronic Journal of Chemistry, 2019)
Of the renewable energy sources, which are less polluting and with the same efficiency of petroleum products, we highlight biodiesel, a renewable and promising source of clean energy, which is now being added in small quantities to commercial diesel used in diesel cycle engine. However, it is necessary to evaluate several factors, so that the amount of biodiesel in the diesel is increased, among them the physicochemical properties of the biodiesel and its mixtures with the commercial diesel, so that they are according to specification of the National Petroleum Agency (ANP) besides the corrosion that it can cause to the constituents of the motor, when in contact. Thus, this work had as main objective to verify the existence of a corrosive process in diesel engine piston when in contact with commercial diesel, biodiesel, and its mixtures, in different proportions and temperatures. For this, initially accomplished the biodiesel synthesis and the characterizations physiochemical of the same. Posteriorly, got it forty-four samples, which were immersed in the pure biodiesel (B100) and its mixtures with commercial diesel in the proportions of 7, 10, 20, 30, 40, 50, 60, 70, 80, and 90% in different temperatures, after the immersion tests, it was calculated the corrosion rate present and analysis of the samples with the help of the scanning electron microscopy (SEMA), that were analyzed through of the ImageJ program. After analysis, it can be concluded that the biodiesel synthesized had the properties within the limits established by the ANP, that the corrosion in the material that compose the engine piston in the studied period was low for all the mixtures used. Therefore, it is suggested that the biodiesel obtained in this work and itis respective mixtures are viable as alternative renewable sources to be applied as fuel in engines.DOI: http://dx.doi.org/10.17807/orbital.v11i5.1404